Блокчейн як засіб забезпечення безпеки в цифровому світі - Поліщук, В. Г. (ХНУРЕ, 2023)
This work is focused on the importance of security in blockchain technology, highlighting its decentralized nature and resistance to cyberattacks. The text explains the key concepts of consensus and immutability, which play crucial roles in ensuring data integrity and transaction reliability. Additionally, the role of cryptography, specifically hashing, is discussed as an essential element in maintaining the security of data within blockchain technology. The combination of these features contributes to the overall security and dependability of blockchain systems